Механотронная система АСУ ТП шахтного назначения - Гарганеев, А.Г.; Гарганеев, Б.П.; Каракулов, А.С.; Коломенский, О.И.; Машинский, В.В. (Технічна електродинаміка, 2012)
The paper presents the issue of mechanotronic system to control pipeline vales for mine applications. Based on the pipeline valve performance requirements and the operation mode peculiarities, the applicability of various electrical machines and semiconductor converters in mechanotronic systems is analyzed. Functional diagram of mechanotronic system is provided. The control features of microprocessor mechanotronic system are presented